Asbestos fiber identification in liver from cholangiocarcinoma patients living in an asbestos polluted area: a preliminary study. Issue 5 (October 2019) - Grosso, Federica; Croce, Alessandro; Libener, Roberta; Mariani, Narciso; Pastormerlo, Massimo; Maconi, Antonio; Rinaudo, Caterina
Purpose: To assess whether asbestos fibers may be observed in liver tissue of patients with cholangiocarcinoma (CC) with environmental or working asbestos exposure. Methods: Detection of fibers was performed directly on histologic sections of liver from 7 patients with CC using optical microscope and variable pressure scanning electron microscopy equipped with energy-dispersive spectroscopy (VP-SEM/EDS). All patients were from Casale Monferrato, Italy, a highly asbestos-polluted town. Due to ethical constraints, observers were blinded to patients' clinical features. Results: Fibers/bundles of fibers of chrysotile were detected in 5 out of 7 patients (71%). The boundary between healthy and neoplastic tissue or the fibrocollagen tissue produced by the neoplasia were identified as areas of fiber incorporation. Conclusions: This study is the first report about the detection of chrysotile asbestos fibers in the liver of patients with CC. Further studies on larger cohorts are needed to corroborate our preliminary findings.